The business case for enterprise-class wireless Lans - Castaneda, H. David (Cisco Press, 2006)
A comprehensive guide to analyzing the business rationale for WLANs Evaluate the business rationale behind the deployment of WLANs, including return on investment (ROI), net present value, payback period, and total cost of ownership Develop a robust execution plan to deploy and operate the WLAN Understand the high-level technical issues of deploying and managing your WLAN from a business decision-maker's perspective Maximize the positive impact of supplementary and complementary services such as voice, video, and guest WLAN access Identify potential security threats and develop strategies to mitigate attacks Learn methodological and technical best practices from WLAN deployment case studies featuring real-world, enterprise-class businesses and institutions Gather information easily by referring to quick reference sheets and appendixes covering an antenna overview, a high-level sample project plan, checklists, and flowcharts Businesses today are increasingly adopting wireless LANs (WLANs) as a primary data transport mechanism. To determine when and how to effectively deploy WLANs, business managers, project managers, and IT executives need a clear, holistic evaluation of the business benefits and risks behind this complex technology solution. The Business Case for Enterprise-Class Wireless LANs helps you make the right decisions by explaining the business value and cost of investing in a WLAN-from security and architecture to deployment and application. Using a lifecycle perspective, this guide covers the value proposition, cost justification, and alignment of security, design, and operational components within the business. Written in an approachable style, The Business Case for Enterprise-Class Wireless LANs provides a baseline analysis of WLAN technologies for a large-scale deployment and includes concise real-world case studies with checklists and flowcharts that you can adapt for your needs. By recognizing the obstacles and advantages of implementing a WLAN from a strategic and justified business perspective, you can apply the economic benefits to your organization and ensure a timely and efficient deployment of your organization's WLAN. This volume is in the Network Business Series offered by Cisco Press®. Books in this series provide IT executives, decision makers, and networking professionals with pertinent information about today's most important technologies and business strategies.